English as Lingua Franca: Teachers’ Perception Toward English Varieties in Teaching English as Foreign Language - Novira Anjani; Iwan Setiawan; Bibit Suhatmady (Universitas Muhammadiyah Tangerang, 2025)
English Language Teaching (ELT) in English as Foreign Language (EFL) countries is not far from the concepts of English as Lingua Franca (ELF). This study aimed to investigate how teachers’ perception toward English varieties in ELT. This study carried out using qualitative design with interview as the instrument. This research involved three teachers of Senior High School in Kutai Kartanegara with different schools, backgrounds, and experiences. There were three aspects discussed; teachers’ perception towards native speaker model, teachers’ perception on variations of English, and teachers’ perception on ELF and cultural understanding. The results showed English teachers still oriented to native speaker’s model since the goal of learning English refers to English proficiency in standard English. However, the teachers were also aware with the English variations which was used globally. This research contributed the consideration of incorporating the idea of native speakerism and ELF into English language teaching.